Development finance in the global economy : the road ahead - Addison, Tony.; Mavrotas, George; World Institute for Development Economics Research (Basingstoke [England] ; New York : Palgrave Macmillan, 2008)
This book explores how international finance can serve the needs of poor countries and poor people, including chapters on multilateral development assistance, multi-actor global funds, and the transition from official development assistance to private capital flows.
"In association with the World Institute for Development Economics Research of the United Nations University (UNU-WIDER)."
Includes bibliographical references and index.
rua 31/10/13
Loans
Keywords: Finance -- Developing countries; Economic development -- Developing countries; Economic assistance -- Developing countries